Domestication and Foreignization of Hyperbole in Donald Duck’s Comic From English to Indonesian - Gina Aulia; Hayatul Cholsy (Universitas Indo Global Mandiri, 2025)
Abstract Translating comics presents unique challenges, particularly due to the rich cultural elements embedded in the source language. This study explores the translation strategies applied to hyperbolic expressions in the Donald Duck comic series. The current study uses a descriptive analysis method. The analysis reveals that domestication is the predominant strategy employed. By utilizing domestication, the translator adapts cultural references to align with the norms and expectations of the target audience, thereby enhancing readability and familiarity. However, this approach often leads to a reduction or loss of the original hyperbolic effect, as the translated text tends to emphasize the underlying meaning or contextual relevance over a literal preservation of rhetorical devices. While domestication facilitates pragmatic equivalence and audience engagement, it may compromise the stylistic and emotive force of the original text, highlighting the tension between cultural accessibility and rhetorical fidelity in comic translation Keywords: Hyperbole, Comic translation strategy, Domestication, Foreignization